2009
DOI: 10.1111/j.1574-6976.2009.00180.x
|View full text |Cite
|
Sign up to set email alerts
|

Fungal apoptosis: function, genes and gene function

Abstract: Cells of all living organisms are programmed to self-destruct under certain conditions. The most well known form of programmed cell death is apoptosis, which is essential for proper development in higher eukaryotes. In fungi, apoptotic-like cell death occurs naturally during aging and reproduction, and can be induced by environmental stresses and exposure to toxic metabolites. The core apoptotic machinery in fungi is similar to that in mammals, but the apoptotic network is less complex and of more ancient orig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
155
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(160 citation statements)
references
References 186 publications
(271 reference statements)
2
155
0
3
Order By: Relevance
“…Authors have also reported ROS-induced apoptosis in Aspergillus nidulans, Fusarium oxysporum, and Candida albicans cells (37)(38)(39). Sharon et al (40) reported that apoptotic pathways in fungi seem to be mitochondrion dependent, and mitochondria are considered to be a powerful source of superoxide radicals in miconazole-and farnesol-induced apoptosis (41). …”
Section: Discussionmentioning
confidence: 99%
“…Authors have also reported ROS-induced apoptosis in Aspergillus nidulans, Fusarium oxysporum, and Candida albicans cells (37)(38)(39). Sharon et al (40) reported that apoptotic pathways in fungi seem to be mitochondrion dependent, and mitochondria are considered to be a powerful source of superoxide radicals in miconazole-and farnesol-induced apoptosis (41). …”
Section: Discussionmentioning
confidence: 99%
“…S2 in the supplemental material). As high temperatures induce both apoptosis and necrosis in mammalian cells (15), we sought to differentiate between apoptotic and necrotic R. oryzae cells by using the annexin V-FITC and PI double-staining method. In this method, apoptotic cells are stained with annexin V-FITC, whereas PI accumulates in the nuclei of necrotic cells via membrane permeabilization (34).…”
Section: Resultsmentioning
confidence: 99%
“…Various physiological stresses, ionizing radiation, and hyperthermia have been reported to trigger apoptosis in fungi and cancer cells (14)(15)(16). However, the precise mechanism of hyperthermia-induced apoptosis in mammalian cells is not clear.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although necrotic cell death is possible during any kind of stress, programmed cell death processes have also been observed during carbon starvation in several fungi (Emri et al, 2005;Cebollero & Gonzalez, 2006;Robson, 2006;Pollack et al, 2009;Sharon et al, 2009). In the case of A. nidulans, the appearance of apoptotic markers (membrane inversion, DNA fragmentation) was detected in late autolytic cultures, and macroautophagy has also been observed in both carbon-starved and rapamycin-treated cultures by Emri et al (2005) and Kim et al (2011), respectively.…”
Section: Programmed Cell Death During Carbon Starvationmentioning
confidence: 99%